Upaya Hukum dalam Pencegahan Praktik Pencucian Uang melalui Penerapan Know Your Customer - Nurul Azizah; Agustianto; Shenti Agustini (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This study examines the legal framework and implementation of Know Your Customer (KYC) in preventing money laundering and analyzes the adequacy of its regulations, using a juridical-empirical approach through observations and interviews with banking practitioners and financial services regulators in Batam, analyzed using Soerjono Soekanto’s Theory of Legal Effectiveness. The results show that KYC is regulated in multiple layers and implemented through riskbased customer identification, verification and monitoring; however, its implementation is hampered by technological and human resource gaps, regulatory overlap and a lack of individual sanctions. This study recommends regulatory harmonization, strengthening KYC rules for fintech, strict sanctions for negligent employees, improvements in technology and human resources for rural banks (BPRs) and public education to foster a culture of compliance.